An electromyographic study on antagonistic muscle regulation in the judoist - Masuda, M.; Shibayama, H.; Ebashi, H. (Association for the Scientific Studies on Judo, Kodokan, 1972)
With the development of kinesthiology, quite a number of literature regarding electromyographic (EMG) studies of various Judo techniques has been published, since Ikai first reported on his EMG studies of Nage Waza (throwing technique). The study of muscular work, i.e., muscular contraction and its associated tension is very helpful in making a scientific analysis of the various techniques of Judo. The leads generally used for EMG studies during the actual practice of Judo are surface leads because they must be able to withstand violent body movement, and consequently, most studies concern acting muscle groups. The value of these EMG studies as a useful adjunct in muscle training has been recognized, and Karpovich has already made many relevant investigations. In order tofully understand the significance of the records of the EMG taken by the surface lead method during actual Judo practice, an analysis of simplified body movement is also necessary. With this in mind the authors selected a most simplified action and made an EMG study of it as an adjunct to the investigation of muscular movement in Judo, or for that matter voluntary muscular movement in general. The authors made the study from the viewpoint of antagonistic muscle action which deter mine muscle strength. The voluntary muscular movement, such as in Judo, may be considered to be acollectiveaction of a group of simple muscular contractions and consequently exhibit the properties of skeletal musclesi. A. V. Hill using the sartorius muscle of the frog studied the relation of strength and velocity of muscular contraction and formulated a characteristic equation which may be expressed by a rectangular hyperbole. For example, a muscle does a large amount of work during low velocity contraction against high resistance. In voluntary muscular movement, such as those seen in Judo, these characteristics of skeletal muscles do not manifest themselves in their pure form. The excitability of the motor unit is increased by the activity of the central nervous System, particularly by that of the motor area of the cerebral cortex, and the activity of large muscle groups is determined by the number of motor units participating and on the frequency of Stimulation. Consequently, the activity of the protagonistic muscle which is the chief constituent of voluntary muscular movement, depends mostly on the characteristics of the muscles concerned, however, the activity of the antogonists depend mostly on the central nervous System. In order to investigate this mutual antagonism, a study was made on simplified body movement.